2022
DOI: 10.15237/gida.gd21123
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Malt Flours on Rheological Properties of Dough

Abstract: The present work explored the effect of malt flours obtained from different grains (wheat, barley, rye, triticale, millet, maize, rice, oat) on rheology, fermentation and pasting properties of wheat dough. Malt flour and commercial enzyme added to bread flour decreased peak viscosity and peak temperature values measured in Amylograph. Wheat, rye and oat malt flours provided the best result, respectively, in terms of farinogram properties of flour samples such as water absorption, development time, dough stabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The results showed that with the addition of BMF, DS significantly decreased, which might have occurred due to disturbance in natural wheat gluten network, caused by fibers of BMF. Czubaszek et al (2022) performed experiments to analyze the effect of the addition of barley brewers spent grains on flour for bread In another relevant structure study, Karaoglu et al (2022) studied the influence of various malt flours, including rye, maize, rice, barley, and oat malt, on the rheological qualities of the dough. The addition of malt flours led to more stable dough when compared to commercial enzymes, as the malting process enhances the natural α-amylase presence and activity in barley flour.…”
Section: Dough Stability Of Wheat Flour Supplemented With Barley Malt...mentioning
confidence: 99%
“…The results showed that with the addition of BMF, DS significantly decreased, which might have occurred due to disturbance in natural wheat gluten network, caused by fibers of BMF. Czubaszek et al (2022) performed experiments to analyze the effect of the addition of barley brewers spent grains on flour for bread In another relevant structure study, Karaoglu et al (2022) studied the influence of various malt flours, including rye, maize, rice, barley, and oat malt, on the rheological qualities of the dough. The addition of malt flours led to more stable dough when compared to commercial enzymes, as the malting process enhances the natural α-amylase presence and activity in barley flour.…”
Section: Dough Stability Of Wheat Flour Supplemented With Barley Malt...mentioning
confidence: 99%
“…1% to improve the amylolytic potential of baking mixtures and thus improve the technological and sensory characteristics of the final product [1,[24][25][26]. Karao glu et al [27] reduced the falling number of wheat flour from 539 s to the optimal value (274 ± 3 s) using the mixture of wheat flour with various types of malt (from cereals and pseudo-cereals) in amounts from 0.570 to 1.902% and commercial enzyme in the amount of 0.0115%. These researchers found that in terms of the rheological properties of the dough, the use of malt flour as a source of enzymes gave better results than the commercially available enzyme.…”
Section: Introductionmentioning
confidence: 99%
“…These researchers found that in terms of the rheological properties of the dough, the use of malt flour as a source of enzymes gave better results than the commercially available enzyme. In addition to improving the rheological characteristics of the dough, the addition of malt had a positive effect on the fermentation properties of the dough, such as increasing the fermentation speed, the ability to retain gases, and a larger volume of the bread loaf [3,[27][28][29]. Malt also contributes to an increase in the content of reducing sugars, which may lead to a greater intensity of the Maillard reaction [25,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation